1997
DOI: 10.1118/1.598085
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in radiotherapy treatment planning

Abstract: The aim of this study is to investigate the capabilities of magnetic resonance imaging (MRI) in radiotherapy treatment planning (RTP) and to explore the MR image distortions and how these distortions can be reduced or, if necessary, corrected in order to integrate MRI into RTP in a reliable manner. Image distortions and the efficacy of correction methods were evaluated in phantom, volunteer, and patient studies. From the measurement, analysis, and correction of machine‐related geometric distortions in MRI, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…In a clinical setting, these acquisition parameters are readily changeable in order to obtain an image of required quality for the purposes of planning, however the trade-offs between SNR and distortion values need to be considered. It was assumed for each acquisition sequence, with the same setup that the distortion values were reproducible[23].The distortion maps inFigs. 2 and 3can be compared to the position within which various clinical sites lie with respect to the centre of the scanner(Fig.…”
mentioning
confidence: 99%
“…In a clinical setting, these acquisition parameters are readily changeable in order to obtain an image of required quality for the purposes of planning, however the trade-offs between SNR and distortion values need to be considered. It was assumed for each acquisition sequence, with the same setup that the distortion values were reproducible[23].The distortion maps inFigs. 2 and 3can be compared to the position within which various clinical sites lie with respect to the centre of the scanner(Fig.…”
mentioning
confidence: 99%
“…A correction for those distortions is not necessary, provided that the volume of interest, which contains the target volume and the markers and which has typical dimensions of 10 cm in all directions, is at the center of the magnet. Susceptibility-induced distortions, which result in small shifts of the markers, are reduced to less than 1 mm by imaging at a magnetic field strength of 0.5 T and using gradient strengths on the order of 3 mT/m [28]. The metal of the skull screws produces limited artefacts just around the screws.…”
Section: B Geometrical Accuracy Testmentioning
confidence: 99%
“…These pertubations are caused by an inhomogeneous susceptibility distribution [34], in this case mainly by the difference in susceptibility between the head and the Perspex of the imaging template at one side and the surrounding air at the other side. Our aim to keep the spatial image distortion below 1 mm, can be fulfilled according to Moerland [28]. He has shown that the system related spatial distortions are less than 1 mm in the center of the magnet.…”
Section: B Geometrical Accuracy Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments were performed with a flow phantom consisting of 77 serially connected, parallel tubes placed in a regular matrix ( Fig. 2) (13). The phantom could be rotated in the scanner bore, such that the tubes were either parallel or perpendicular to the main field.…”
Section: The Flow Phantommentioning
confidence: 99%